Rancang Bangun Media Bantu Pemeriksa Penyimpangan Pada Poros - Robert Napitupulu; Rodika Rodika; Febrian Arif; M Romario4; Reni Febrianti (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
Machine Improvement Element (PEM) is one of the competencies that must be possessed by students Polytechnic Manufacturing of Bangka Belitung (PolmanBabel), in the hope that the students can repair the damage of machine element such as the shaft, peg, gear and thread well. Currently the process of repairing the engine element is constrained in the inspection tools of mesi element improvement such as the shaft. This study aims to design auxiliary media for aberration checks on the axis and can examine alignment and alignment deviations on axis. The stages of this research starts from the collection of data and information, then designing tools, making tools, assembling, and testing. Based on the results of design and testing of the aberration check axis on the axis obtained the magnitude of averages 0.23mm and the magnitude of deviation celery averages of 0.12.